Gestational diabetes is associated with postpartum hemorrhage in Indigenous Australian women in the PANDORA study: A prospective cohort. Issue 2 (19th August 2021) - Lucas, Isabelle M.; Barr, Elizabeth L. M.; Barzi, Federica; Longmore, Danielle K.; Lee, I‐Lynn; Kirkwood, Marie; Whitbread, Cherie; Connors, Christine; Boyle, Jacqueline A.; Simon, David; Goodrem, Adeliesje; Brown, Alex D. H.; et al.
Abstract: Objective: To assess associations of hyperglycemia in pregnancy with the risk of postpartum hemorrhage (PPH) in a prospective cohort of Indigenous and non‐Indigenous women, compared with normoglycemia. Methods: Data were from 1102 (48% Indigenous) women of the Pregnancy And Neonatal Diabetes Outcomes in Remote Australia (PANDORA) Study. Age‐adjusted associations of gestational diabetes mellitus (GDM) or pre‐existing type 2 diabetes mellitus (T2DM), obstetric and demographic covariables with PPH (blood loss ≥500 ml) were assessed using logistic regression. Multivariable‐adjusted models included Indigenous ethnicity, diabetes type and their interaction. Results: A higher proportion of Indigenous women developed PPH than non‐Indigenous women (32% versus 22%; P < 0.001). Compared with non‐Indigenous women with normoglycemia, risks of PPH for Indigenous women with GDM or T2DM were higher (odds ratio [OR] 1.83, 95% confidence intervals [CI] 1.11–3.02, and OR 1.72, 95% CI 0.99–3.00 after age adjustment, OR 1.84, 95% CI 1.06–3.19, and OR 1.33, 95% CI 0.70–2.54 after adjustment for school education and delivery mode, and OR 1.62, 95% CI 0.95–2.77, and OR 0.99, 95% CI 0.53–1.86 after adjustment for birth weight). Importantly, Indigenous women without hyperglycemia in pregnancy were not at increased risk of PPH. Conclusion: The significantly higher rates of PPH experienced by Indigenous women compared with non‐Indigenous women may be explained by a greater effect of GDM among Indigenous women that was only partly accounted for by birth weight. Synopsis: Higher risk of PPH experienced by Indigenous than by non‐Indigenous Australian women may be explained by a greater effect of GDM among Indigenous women.